2020
DOI: 10.1111/den.13809
|View full text |Cite
|
Sign up to set email alerts
|

Multimedia based education on bowel preparation improves adenoma detection rate: Systematic review & meta‐analysis of randomized controlled trials

Abstract: Background and Aims Colorectal cancer (CRC) is the third most common cause of cancer worldwide. Studies have shown a strong association between screening colonoscopy and a reduced risk of death from colorectal cancers. The incidence of poor bowel preparation has been reported in up to 25% cases. We conducted a systematic review and comprehensive meta‐analysis to evaluate the effect of patient education using multimedia platforms on adenoma detection rate and adequacy of bowel preparation. Methods Multiple data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 54 publications
1
11
0
Order By: Relevance
“…Considering that bowel preparation is not limited to colonoscopy and reinforcement methods are not necessarily named "education", we did not use "colonoscopy" and "education" as search terms to avoid omission. This is also consistent with several related meta-analyses published previously [ 25 , 26 , 41 , 42 ]. Due to the obvious heterogeneity (I 2 = 87%, p <0.00001), we analyzed the source of the heterogeneity.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Considering that bowel preparation is not limited to colonoscopy and reinforcement methods are not necessarily named "education", we did not use "colonoscopy" and "education" as search terms to avoid omission. This is also consistent with several related meta-analyses published previously [ 25 , 26 , 41 , 42 ]. Due to the obvious heterogeneity (I 2 = 87%, p <0.00001), we analyzed the source of the heterogeneity.…”
Section: Discussionsupporting
confidence: 93%
“…Examples included cartoon education booklets [ 12 , 13 ], educational videos [ 14 16 ], smartphone applications [ 17 , 18 ], telephone communication [ 7 , 19 21 ] and message reminders [ 22 24 ]. A recent meta-analysis showed that multimedia education can increase the rate of adequate bowel preparation and the detection rate of adenomas during colonoscopy [ 25 ]. A meta-analysis published in 2017 showed that these methods improved the quality of bowel preparation for colonoscopy [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…e quality of colonoscopy is the cornerstone of surveillance colonoscopy program, which is associated with several factors, such as bowel preparation, withdrawal time, endoscopists ' experience, and patients' cooperation [5]. Among these, a high-quality bowel preparation is a critically determinant factor to improve adenoma detection rate (ADR) and reduce the incidence of CRC [6]. Inadequate bowel preparation will lead to prolonged procedure duration, decreased visibility of the colonic mucosa, and low ADR [7].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, telephone follow‐up, short‐message service, and smartphone applications have been widely used to improve health outcomes in various fields because of the cost‐effectiveness and convenience 29‐31 . Several studies 29,32,33 have shown that pre‐colonoscopy patient education using telephone follow‐up, smartphone applications, short‐message service, and online audio‐visual aids could improve the adequacy of bowel preparation and polyp detection rate. Numerous studies 30,34 have also reported that smartphone apps show unique advantages in the management of chronic diseases such as hypertension and diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, telephone follow-up, short-message service, and smartphone applications have been widely used to improve health outcomes in various fields because of the cost-effectiveness and convenience. [29][30][31] Several studies 29,32,33 have shown that pre-colonoscopy patient education using telephone follow-up,…”
Section: Discussionmentioning
confidence: 99%